초초임계압 발전소 확대에 따른 CO₂ 감축잠재량 연구 - 노준영(Roh, Joon Young); 강성민(Kang, Sung Min); 이화수(Lee, Hwa Su); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2020)
In this study, the CO2 emission factors of supercritical and ultra-supercritical power plants considering the transmission stage efficiency were calculated. The CO2 reduction potential was calculated for the ultra-supercritical power plant, which was introduced up to 40%. The CO2 emission factor of the supercritical power plant was 1.017 kg CO2/kWh, while the emission factor of the ultra-supercritical power plant was 0.947 kg CO2/kWh. Thus, the emission factor of the ultra-supercritical power plant was estimated to be about 7% lower. By calculating the CO2 emissions according to the supercritical and ultra-supercritical power generation ratio, we found that when the power generation ratio of the ultra-supercritical power generation increased to 40%, the CO2 emissions decreased by 1.74% (4,906,117 tons of CO2). KCI Citation Count: 0